Determination of Principal Yield Attributing Traits of Hybrid Maize (Zea mays L.) Using Multivariate Analysis - Rana, L.; Banerjee, H.; Mazumdar, D.; Sarkar, S.; Ray, K.; Garai, S.; Nayek, J.; Kumar, M. (International Journal of Bio-resource and Stress Management, 2021)
The field experiments were conducted at farmer’s field, Madandanga village under Chakdaha Block of Nadia district in West Bengal during rabi season 2014-15 and 2015-16. Treatments were distributed in split-factorial design, with three varieties (P ‘3533’, P ‘3396’, P ‘30V92’) in the main plot and three planting density (55,555, 66,666, 83,333 plants ha-1) × three sowing dates (November 20, November 30, December 10) combinations in the sub-plots, replicated thrice. Irrespective of planting density and sowing date, the variety ‘P30V92’ produced the highest yield, followed by ‘P3396’ and ‘P3533’. The significantly highest grain and stover yield was obtained in high density planting (83,333 plants ha-1), accounting 44.2 and 39.6% more than low planting density (55,555 plants ha-1), respectively. The maximum grain and stover yields were obtained from Nov. 20 sown plants; being 7.71 and 11.95% more than the grain yield derived from late sown (Dec. 10) plants. A correlation study showed that among the growth and yield components, leaf area index (0.96) and shelling percentage (0.91) exhibited highly positive direct effects on the grain yield of hybrid maize. However, other growth attributes, namely P uptake (0.88), K uptake (0.86) and plant height (0.81) exerted comparatively low positive direct effects on the grain yield of hybrid maize. Further, the standard regression equation revealed a significant relationship of shelling percentage (p≤0.01), leaf area index (p≤0.01) and uptake of P (p≤0.05) with grain yield.